Daya Dukung Lahan Pertanian Di Kabupaten Kendal - Noor Malita Dwirani; Trida Ridho Fariz; Fadya Elva Riani; Nadira Safitri; Alisa Faidatul Umam; Abdul Jabbar; Fathia Lutfiananda (Universitas Tanjungpura, 2022)
Kendal Regency is one of the regencies in Central Java which is a center for rice production and has a fairly large area of rice fields. The study of the carrying capacity of agricultural land is very important because it is part of the study of the carrying capacity of the environment (D3TLH). Among the achievements of research on the carrying capacity of agricultural land, there has not been much discussion about the limitations and how to improvise the method. Therefore, this article will try to analyze and discuss the carrying capacity of agricultural land in Kendal Regency. The data used is secondary data from Kabupaten Kendal Dalam Angka. The results of the analysis show that Kendal Regency has a carrying capacity of 1.74 agricultural land which means a surplus. The limitation of this agricultural land carrying capacity analysis method is that it is difficult to model the carrying capacity of ecoregion-based agricultural land. Therefore, in the future work, we can build pixel-based data through remote sensing such as rice productivity extracted from the NDVI and EVI vegetation indices.